ANALISIS PELAKSANAAN BAURAN PROMOSI PADA PT. ANGKASA RAYA TALUK KUANTAN - Erlina, Dosma; Zuliarni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research have done in PT. Angkasa Raya Taluk Kuntan Setting of the problem is how implementation diffusivity are promotion in PT.Angkasa Raya Taluk Kuantan. The purpose of this research is too find out implementation of diffusivity promotion in PT. Angkasa Raya Taluk Kuntan and to find out the obstacles found.Using use descriptive analysis method and some theories about Analysis implementation. Indicator used of this research are Tangibles, advertising, sales promotion, personal selling, direct marketing, and publisitas assurance as measurement of analysis implementation diffusivity promotion in PT.Angkasa Raya Taluk Kuantan. Data collecting technique is done by interview, observation and quisioner. Sampling is done by sampling accidental. Data sources devided in to two: primary, which is gotten from questioner,observation and interview. Another one is secondary data, which is gotten from documents in PT.Angkasa Raya Taluk Kuntan The result shows that diffusivity promotion in PT. Angkasa Raya Takuk Kuantan is categorized as good .Keyword: promotional mix, Advertising, Sales Promotion, Personal Selling, Direct Marketing, And Publicty.